2021
DOI: 10.3390/biom11091314
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Interaction of Lysosomal Amino Acid Transporters SLC38A9 and SLC36A1 Involved in mTORC1 Signaling in C2C12 Cells

Abstract: Amino acids are critical for mammalian target of rapamycin complex 1 (mTORC1) activation on the lysosomal surface. Amino acid transporters SLC38A9 and SLC36A1 are the members of the lysosomal amino acid sensing machinery that activates mTORC1. The current study aims to clarify the interaction of SLC38A9 and SLC36A1. Here, we discovered that leucine increased expressions of SLC38A9 and SLC36A1, leading to mTORC1 activation. SLC38A9 interacted with SLC36A1 and they enhanced each other’s expression levels and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…A previous study reported that the SLC38A9 protein interacts with SLC36A1 proteins on the lysosomal surface, and these transporter complexes enhance each other’s expression levels. 36 Expectedly, NRF3 knockdown reduced the gene expression of SLC36A1 under amino acid or arginine stimulation ( Figure 3 D). Also, we observed that the SLC36A1 promoter contained an ARE region, where NRF3 proteins were potentially recruited ( Figures 3 E and S3 B).…”
Section: Resultsmentioning
confidence: 89%
“…A previous study reported that the SLC38A9 protein interacts with SLC36A1 proteins on the lysosomal surface, and these transporter complexes enhance each other’s expression levels. 36 Expectedly, NRF3 knockdown reduced the gene expression of SLC36A1 under amino acid or arginine stimulation ( Figure 3 D). Also, we observed that the SLC36A1 promoter contained an ARE region, where NRF3 proteins were potentially recruited ( Figures 3 E and S3 B).…”
Section: Resultsmentioning
confidence: 89%
“…It exerts a variety of important physiological functions, including promoting nutrient absorption, controlling nutrient recycling, and activating the mTORC1 signaling pathway [36]. In a study by Wang et al (2021), SLC36A1 mediated the activation of mTORC1 induced by leucine [37]. Therefore, SLC36A1 in DM may play a role in the nutrient's absorption and signal transduction, which requires further research.…”
Section: Nutrition and Transportationmentioning
confidence: 99%
“…In this regard, several solute carriers (SLCs) have been reported to be involved in the transport of AAs across lysosomal membranes, some of which could potentially contribute to these non-specific currents. Possible candidates include, SLC38A9 [34,35], LYAAT1 (SLC36A1) [34,36] PQLC2/LAAT1 (SLC66A1) [34,37] and SNAT7 (SLC38A7) [34,38], and less likely, as it is mainly expressed in immune cells, PHT2 (SLC15A3) [39]. Regarding captopril-induced nonspecific currents, it has been shown that certain drug efflux transporters, such as the ABC transporter TAPL (ABCB9), may be involved in peptide transport across lysosomal membranes [40,41].…”
Section: Substrate Selectivitymentioning
confidence: 99%